Fiscal Sustainability, Volatility and Oil Wealth: A Stochastic Analysis of Fiscal Spending Rules - Sweder van Wijnbergen; Nina Budina (Tinbergen Institute, 2011)
Whether fiscal policy is sustainable depends on a government's future revenue and expenditure streams, both of which are highly uncertain. In commodity-rich countries, this problem is intensified by unpredictable and volatile commodity prices. We show how spending rules for oil income and non-oil primary deficits interact and influence the stochastic distribution of future debt stocks and demonstrate the variance reducing impact of feedback rules for primary deficits in a case study of oil-and-gas exporter Azerbaijan.
Keywords: E21; E27; 330; volatility; oil wealth; fiscal sustainability; Ölpreis; Volatilität; Öffentliche Einnahmen; Schock; Finanzpolitik; Nachhaltigkeit; Aserbaidschan